Pembelajaran Fiqih di Madrasah Ibtidaiyah Al-Asyhar Jelu Ngasem Bojonegoro - Zumrotus Sa’diyah; Firda Zakiyatur Rofiah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This study discusses the implementation of fiqh learning at Madrasah Ibtidaiyah Al Asyhar Jelu Ngasem Bojonegoro and the factors that influence it. The subject of this research is one teacher of fiqh and students at Madrasah Ibtidaiyah Al Asyhar Jelu Ngasem Bojonegoro and the object of this research is the implementation of fiqh learning at Madrasah Ibtidaiyah Al Asyhar Jelu Ngasem Bojonegoro. To obtain data, the researcher used observation, interview and documentation techniques. The data processing technique is done by editing, data classification and data interpretation. Furthermore, it is analyzed by qualitative descriptive analysis and deductive conclusions are drawn. From the results of this study, it was obtained an overview of the implementation of fiqh learning at Madrasah Ibtidaiyah Al Asyhar Jelu Ngasem Bojonegoro, namely the planning of learning fiqh has been carried out well, because the teacher makes annual programs, semesters, syllabus and lesson plans (RPP). Fiqh learning was carried out well, because at the time of delivery of subject matter with appropriate and varied methods and the use of media even though the media was very limited. The evaluation was carried out well, the teacher carried out pre-test, post-test, and assessment of the process and results. The factors that influence the learning of fiqh such as the background is in accordance with the field being taught and the teaching experience is quite long. Student interest is quite good, because students are quite active in the learning process. The environment outside the school is very supportive of the fiqh learning process. While the factors of facilities and infrastructure are quite complete but rarely used.